Open the door...let the breeze in - Nithyananda (Bangalore, 2005)
Open the door let the breeze in! is a series of thought-provoking articles that focus on the science of inner transformation in contemporary society. Compiled from talks given by swamiji to audiences in India and Abroad and throwing light on issue of prime relevance in our time, these articles equip you with practical, active tools for more joyful living.
Keywords: Spiritual life